A Meta-Analysis on Factors Affecting Succession Management in Public Organizations - Mahdi Janahmadigol; Hamid Rezaiefar; Hossein Hakimpur (پژوهش‌های مدیریت عمومی, 2023)
Extended Abstract Abstract The purpose of this study was investigating the factors affecting succession management in public organizations using meta-analysis. The statistical population includes valid papers in reputable domestic and international databases regarding factors affecting succession management. The collected data were analyzed by CMA2 software. Finally, the results of the study led to the identification of 41 effective factors out from 53 factors studied in the study of succession in organizations. By recognizing these factors, the necessary grounds for purposeful decision making and implementation of appropriate strategies in order to use talented and competent forces are facilitated.IntroductionSuccessful succession management can be effective in retaining staff, preparing high-capacity staff for key positions, and placing key individuals in vacant key positions (Barzegar, Roshan, Bijan, Shahriari & Yaghoubi, 2021). Employee retention is the key to organizational success and market development and leadership (Rowshan, Barzegar & Yaghoubi, 2020). Succession planning has a positive effect on employee engagement and employee performance (Barzegar, Roshan & Yaghoubi, 2020). To date, many studies have been conducted to identify the factors affecting succession management, each of which has yielded different results. However, this paper apply meta-analysis to integrate and validate the wide-ranging results of papers in this topic.Case studyThe statistical population of the study was scientific research articles published in the years 2010 to 2020. In this regard, relevant keywords were used that resulted in 95 national and international articles, of which 27 papers were selected for analysis.Material and methodsData analysis was performed using CMA2 software, and effect size of factors were calculated. Moreover, funnel diagram method was used to measure the diffusion bias and N heterogeneity test was used for the presence of moderating variables.The sampling method is objective, so the studies that had the below criteria were selected as the research sample, which included as follow:The research was conducted quantitatively (this condition eliminated 14 studies)Succession management should have an important role in the paper (This condition deleted 23 studies)The exact number of research statistics should be specified (this condition eliminated 16 researches)The regression coefficient or coefficient of influence of factors on the composition of succession management be precisely introduced (this condition caused the elimination of 15 studies)Discussion and Results The analysis led to the identification of 41 effective factors out from the 53 factors investigated in the study of succession management in organizations. To enhance the effectiveness of succession planning in organizations, the factors that have the greatest effect size should be considered. The most important factors based on effect size are respectively as follow: change management and process management (2.334), preparation and planning (2.174), career path management (1.791), intergenerational succession intention (1.088), managerial competence (1.076), justice (1.073), rational decision making style (1.051) and motivational factor (1.032), Comprehensiveness (0.976), avoidant decision-making style (0.894), psychosocial factors (0.879), foresight (0.828), instant decision-making style (0.814), flexibility (0.803), supervisor support (0.757), context (0.716), religious beliefs (0.679), structural barriers (0.604), individual abilities and skills (0.517), strategic alignment and needs analysis ((0.505).ConclusionDue to the abundance of research in this topic with scattered research methodologies and the lack of a comprehensive pattern for organizations, we applied meta-analysis method to integrate previous paper results. This means the results can be generalized to most organizations either public or private which is one of the most important achievements of this research. Moreover, by measuring and comparing effect size of previous researches, the most important factors affecting the succession management have been identified.All organizations or researchers that want to conduct research in this topic or intend to use the succession management in a satisfactory way can use the mentioned factors in this paper, especially the factors with greater effect size.